SWIMMING AND CRAWLING BEHAVIOUR OF SCHESTOSOMA SPENDAlE (MONTGOMERY, 1906) - Uma Rani,sangeetha (The Bioscan, 2022)
Rotary The behaviour of Schistosoma spindale cercariae during swimming and crawling was studied using video microscopy. The relevance of continuous, forward, backward, spiral, sinusoidal, and intermittent motions in a water medium has been described and investigated. The details of cercaria's swimming behaviour are quickly reviewed. Common observations included both forward and backward swimming modes, the involvement of furcal ramii, and descriptions of the wave pattern of cercaria's body and tail. Cercariae crawled over the substratum during a prolonged period of vigorous swimming. The cercariae's suckers and the elongation and contraction of their body muscles are shown during their crawling habit.